2015
DOI: 10.1186/s12906-015-0570-2
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial evaluation of plants used for the treatment of diarrhoea in a rural community in northern Maputaland, KwaZulu-Natal, South Africa

Abstract: BackgroundZulu people living in the rural area of Maputaland (KwaZulu-Natal, South Africa) rely heavily on medicinal plants for the treatment of diarrhoea. Abundant availability of medicinal plants in the study area offers low cost health care, but scientific validation is needed in order to lend credibility to the traditional use against many ailments including diarrhoeal infections. With this in mind a study was designed to test the in vitro antimicrobial efficacy of 23 plant species which are used for the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 29 publications
2
29
1
1
Order By: Relevance
“…Antibacterial activity was determined by modified agar gel diffusion method [27]. Autoclaved Mueller-Hinton agar (MHA) was poured into sterile Petri dishes and solidified into plate.…”
Section: Antibacterial Activity Assaymentioning
confidence: 99%
“…Antibacterial activity was determined by modified agar gel diffusion method [27]. Autoclaved Mueller-Hinton agar (MHA) was poured into sterile Petri dishes and solidified into plate.…”
Section: Antibacterial Activity Assaymentioning
confidence: 99%
“…A better understanding of these processes supported by ethnopharmacological uses is important for effective diarrhoea management and control in South Africa and Zimbabwe. Previous researchers such as Dambisya and Tindimwebwa (2003) and van Vuuren et al (2015) are of the opinion that there is correlation between socio-demographic factors and the use of antidiarrhoeal medicinal plants in South Africa. Therefore, some of the plant species documented in this study will play an important role as main sources of primary healthcare available and accessible to all the people in South Africa and Zimbabwe, particularly the poor.…”
Section: Treatment Based On Antidiarrhoeals Alone or In Combination Wmentioning
confidence: 99%
“…Previous research in the Eastern Cape province of South Africa where an estimated 72% of the population lives below the poverty line (Thornton, 2009), revealed that diarrhoea is one of the major diseases treated and managed by traditional medicines (Dambisya & Tindimwebwa, 2003). Northern Maputaland in KwaZulu-Natal province is another province characterized by high poverty levels in South Africa where diarrhoea is a major concern and herbal medicines are widely used to manage and treat diarrhoea (van Vuuren et al, 2015). Similarly, gastrointestinal diseases such as cholera, diarrhoea and dysentery are among the most prominent diseases in Zimbabwe resulting in high mortality rate if not treated promptly (Maroyi, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Hutchings et al (1996) documented S. brachypetala as a treatment of acne; however, to the best of our knowledge, no other studies have investigated this plant against the acne-associated pathogen P. acnes. Previous studies on S. brachypetala have focused on diarrhoeal pathogens (Mathabe et al 2006;van Vuuren et al 2015). With the exception of S. aureus, no other studies were found that investigated the effectiveness of S. brachypetala against skin pathogens.…”
Section: Antimicrobial Activity Of Individual Plantsmentioning
confidence: 99%
“…(Asteraceae) and S. birrea were the most frequently mentioned treatments for skin ailments by the lay people of northern Maputaland. The antimicrobial properties of S. birrea have been studied previously and the bark extracts have been found to possess antimicrobial activity against various pathogens (McGaw et al 2000;Eloff 2001;York et al 2012;Naidoo et al 2013;van Vuuren et al 2015). This plant was reported to treat burns, boils and sores independently as well as used in combination with other plants (De Wet et al 2013).…”
Section: Antimicrobial Activity Of Individual Plantsmentioning
confidence: 99%